Similarity Solutions for Hydromagnetic Free Convective Heat and Mass Transfer Flow along a Semi-Infinite Permeable Inclined Flat Plate with Heat Generation and Thermophoresis - Alam, M. S. S.; Rahman, M. M. M.; Sattar, M. A. A. (Nonlinear Analysis: Modelling and Control, 2007)
The problem of steady, two-dimensional, laminar, hydromagnetic flow with heat and mass transfer over a semi-infinite, permeable inclined flat plate in the presence of thermophoresis and heat generation is studied numerically. A similarity transformation is used to reduce the governing non-linear partial differential equations into ordinary ones. The obtained locally similar equations are then solved numerically by applying Nachtsheim-Swigert shooting iteration technique with sixth-order Runge-Kutta integration scheme. Comparisons with previously published work are performed and the results are found to be in very good agreement. Numerical results for the dimensionless velocity, temperature and concentration profiles as well as for the skin-friction coefficient, wall heat transfer and particle deposition rate are obtained and reported graphically for various values of the parameters entering into the problem.
Keywords: hydromagnetic flow; free convection; inclined plate; heat generation; thermophoresis